Citrulline and ADI-PEG20 reduce inflammation in a juvenile porcine model of acute endotoxemia - Vonderohe, Caitlin; Stoll, Barbara; Didelija, Inka; Nguyen, Trung; Mohammad, Mahmoud; Jones-Hall, Yava; Cruz, Miguel A.; Marini, Juan; Burrin, Douglas (Frontiers in Immunology, 2024)
Background: Arginine is a conditionally essential amino acid that is depleted in critically ill or surgical patients. In both pediatric and adult patients, sepsis results in an arginine-deficient state, and depletion of plasma arginine is associated with greater mortality. However, direct supplementation of arginine can result in excessive production of nitric oxide (NO), which can contribute to hypotension and macrovascular hypo-reactivity observed in septic shock. Pegylated arginine deiminase (ADI-PEG20, pegargiminase) reduces plasma arginine and generates citrulline that can be transported intracellularly to generate local arginine and NO, without resulting in hypotension, while maintaining microvascular patency. The objective of this study was to assess the efficacy of ADI-PEG20 with and without supplemental intravenous citrulline to mitigate hypovolemic shock, maintain tissue levels of arginine and reduce systemic inflammation in an endotoxemic pediatric pig model. Methods: Twenty, 3-week-old crossbred piglets were implanted with jugular and carotid catheters as well as telemetry devices in the femoral artery to measure blood pressure, body temperature, heart rate, and respiration rate. Piglets were assigned to one of three treatments prior to undergo a 5 hr lipopolysaccharide (LPS) infusion protocol. Twenty four hours prior to LPS infusion, control (LPS; n=6) pigs received saline, ADI-PEG20 pigs (n=7) received an injection of ADI-PEG20, and 7 pigs (ADI-PEG20+CIT pigs (n=7) received ADI-PEG20 and 250 mg/kg citrulline intravenously. Pigs were monitored throughout LPS infusion and tissue was harvested at the end of the protocol.Results: Plasma arginine levels decreased and remained low in ADI-PEG20+CIT and ADI-PEG20 pigs compared to LPS pigs, but tissue arginine levels in liver and kidney were similar across all treatments. Mean arterial pressure in all groups decreased from 90 mmHg to 60 mmHg within one hour of LPS infusion, but there were no significant differences among treatment groups. ADI-PEG20 and ADI-PEG20+CIT pigs had less CD45+ infiltrate in the liver and lung and lower levels of proinflammatory cytokines in the plasma. Conclusions: ADI-PEG20 and citrulline supplementation failed to ameliorate hypotension associated with acute endotoxic sepsis in pigs but reduced systemic and local inflammation in the lung and liver.